2006
DOI: 10.1096/fj.06-6616com
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ inhibits extravillous trophoblast cell invasion by a mechanism that involves both changes in apoptosis and protease levels

Abstract: uNK cells are a source of IFN-gamma within early human pregnancy decidua. Mechanisms of IFN-gamma inhibition of EVT invasion include both increased EVT apoptosis and reduced levels of active proteases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 43 publications
1
104
0
9
Order By: Relevance
“…Reports have both supported and refuted a direct role for IFNG in regulation of EVT behaviour. We have recently demonstrated that IFNG regulates EVT invasion via mechanisms dependent on increased EVT apoptosis as well as decreased protease activity (Lash et al 2006b). By contrast, a report examining EVT column formation and migration found IFNG to only partially regulate EVT (Hu et al 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Reports have both supported and refuted a direct role for IFNG in regulation of EVT behaviour. We have recently demonstrated that IFNG regulates EVT invasion via mechanisms dependent on increased EVT apoptosis as well as decreased protease activity (Lash et al 2006b). By contrast, a report examining EVT column formation and migration found IFNG to only partially regulate EVT (Hu et al 2006).…”
Section: Discussionmentioning
confidence: 93%
“…uNK cells produce a range of cytokines that have been shown to regulate trophoblast invasion; these include TNF-α, TGF-β1 and IFN-γ, all of which inhibit trophoblast invasion from placental explants (Otun et al, 2003;Lash et al, 2005;Lash et al, 2006a). Recently, Hanna et al (2006) demonstrated that uNK cell supernatants could stimulate isolated cytotrophoblast invasion through matrigel in a mechanism that was partly dependent on IL-8 and IP-10.…”
Section: Functional Investigationsmentioning
confidence: 99%
“…Furthermore, IFNG is targeted to heparan sulfate that is essential for implantation in mice (Kirn-Safran et al 2008), and this may protect IFNG from inactivation and increase its stability (Lortart-Jacob & Grimaud 1991) to allow protracted effects of IFNG on vascular development in decidual tissue. Type I and type II IFNs modify gene expression at implantation sites in rodents to affect the conceptus directly or to exert indirect effects through actions on blood vessels and decidual cells required for successful implantation and pregnancy (Lash et al 2006). …”
Section: Comparative Aspects Of Implantationmentioning
confidence: 99%